CONSUMER BEHAVIOR: BUYING FOR REVENGE IN PHYSICAL STORES AFTER THE END OF RESTRICTIONS CAUSED BY THE PANDEMIC - Busnelo, Maicon Rafael; Gonçalves, Roberto; Vanni Reffatti, Guilherme; Lazzari, Fernanda (Brazilian Journal of Management and Innovation (Revista Brasileira de Gestão e Inovação), 2025)
Objective: To analyze the relationship between the increase in post-restriction consumption and the emerging concept of revenge consumption, connecting this phenomenon to the strategic implications for retail repositioning in the post-pandemic scenario. Design/Method/Approach: A conclusive descriptive research was conducted using Malhotra’s (2021) data collection instrument, with 304 valid respondents from Caxias do Sul, Rio Grande do Sul, Brazil. Exploratory factor analysis was performed using Jamovi software, and six original variables were selected for linear regression analysis. Originality/Relevance: This study addresses the phenomenon of revenge consumption in the context of the Brazilian retail sector, a topic that remains underexplored, and reveals both challenges and opportunities for physical retailers after the pandemic. Key Results/Findings: The main factors driving post-restriction purchases were consumers feeling obliged to shop after physical stores reopened and the sustained perception of high consumption even after restrictions were lifted. Revenge buying behavior reflects both repressed desires and the maintenance of elevated consumption levels in physical retail spaces. Theoretical and Methodological Implications: The study strengthens the theoretical understanding of revenge consumption during crisis periods and uses a quantitative approach grounded in validated instruments and robust statistical analysis, furthering comprehension of this emerging consumer behavior. Contributions to Society and Organizations: The findings highlight important strategic implications for retail businesses, offering valuable insights for repositioning the sector in light of new consumer behavior patterns post-pandemic, ultimately benefiting both organizations and society through a deeper understanding of consumption motivations in this new context.